في تدريس القراءة Mastery Learning مدخل التعلم للاتقان - Khotijah Khotijah (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2017)
This article discusses the mastery learning. In the process of learning to read, learning approach in which requires learners to master completely the whole standard of competence basic competence or the skill of reading. For it takes a pretty, if not then the level of mastery of the competencies of the students is not yet optimal. Mastery learning is an approach to suit the skills of reading because this approach to pay attention to the difference of each learners to learn in accordance with the time required and the desired manner with the guidance of a teacher. Keywords: Mastery Learning, and reading skills